The Correlation Between Higher of Human Interleukin-6 and C-reactive Protein in Female Patients with Diabetes Type 2 - Jasim Mohmmed, Rehab; Badr Manhy Al khaleeli, Abdulmutalb; Habeeb Obaid, Nada (Pure Sciences International Journal of Kerbala, 2024)
Insulin resistance, glucose intolerance, fat deposition, dyslipidemia, and systemic inflammation are all symptoms of type (2) diabetes (T2D). Giving to the Universal Diabetes Confederation, millions of people worldwide will get diabetes. Genetic and environmental variables play a character in the development of T2D. In this investigation, samples were taken from 40 healthy women and 46 female patients with diabetes mellitus type 2. The serum levels of insulin, C-reactive protein, and Human interleukin-6 were measured in all patients and control groups. The results revealed that patient levels of these parameters were significantly more advanced than those in the control group, but the P value was less than 0.001.